Conferralism and Intersectionality: A Response to Ásta’s Categories We Live By - Katharine Jenkins (Journal of Social Ontology, 2022)
The conferralist account of social properties that Ásta develops and defends in Categories We Live By is persuasive in many ways. Conferralism could however do better, by its own lights, at handling the phenomenon of intersectionality. This paper first suggests a friendly amendment to the schema for conferrals that Asta offers. This helps to explain the difficulty concerning intersectionality. Finally, the paper suggests a way of developing the conferralist account that would resolve this difficulty.